1989
DOI: 10.1111/j.1349-7006.1989.tb02247.x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activities of a Novel 9‐Aminoanthracycline (SM‐5887) against Mouse Experimental Tumors and Human Tumor Xenografts

Abstract: The antitumor effects of SM‐5887, a totally synthetic 9‐aminoanthracycline derivative, were evaluated in six murinc experimental tumor systems (P38S, Ehrlich carcinoma, sarcoma 180, Lewis lung carcinoma, B16 melanoma and colon 38) and nine human tumor‐nude mouse systems (one breast cancer, two lung cancers and six gastric cancers). Characteristically SM‐5887 showed excellent antitumor activities, superior to adriamycin (ADR), against human tumor xenografts, although its activities against murine experimental t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 5 publications
1
62
0
Order By: Relevance
“…The AUC values of amrubicinol and amrubicin were calculated by summing trapezoids. The in vivo antitumor activity is expressed as the value of minimal T/C%, from the data of Morisada et al 2) indicates the value for each indicated cell line. R is the correlation coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The AUC values of amrubicinol and amrubicin were calculated by summing trapezoids. The in vivo antitumor activity is expressed as the value of minimal T/C%, from the data of Morisada et al 2) indicates the value for each indicated cell line. R is the correlation coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…2) Amrubicinol, which was found in plasma, normal tissues, and tumor tissues of mice treated with amrubicin, was shown to be much more effective than amrubicin on various human tumor cells in vitro. Moreover, amrubicin was metabolized to amrubicinol in some of the human tumor cell lines, and amrubicinol had a higher activity level inside the cells compared to amrubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Decomposition of an excess amount of 3 under the reaction conditions produced the undesired by-products. We then turned our attention to acylation of 3 with phthal oyl chloride (2). The yield and the purity of the product (4) were found to depend markedly on the ratio of the reagents.…”
Section: Resultsmentioning
confidence: 99%